Aktivitas Antioksidan Ekstrak Etanol Buah Merah (Pandanus conoideus Lam.) dengan Metode FRAP - Wabula, Rheytno Asdin; Dali, Seniwati; Widiastuti, Harti (Window of Health : Jurnal Kesehatan, 2019)
Red fruit (Pandanus conoideus Lam.) Is an endemic plant that grows in the Papua region. Based on previous research, red fruit contains several active compounds with a fairly high level, including carotenoids, tocopherol, beta-carotene, Î± tocopherol, and fatty acids such as oleic acid, linoleic acid, linolenic acid, and dexoic acid. The high tocopherol content in red fruit has antioxidant activity. This study aims to determine the antioxidant capacity of the ethanol extract of red fruit (Pandanus conoideus Lam.) Using the FRAP method. Three replications of red fruit ethanol extract were measured for antioxidant capacity using standard Î±-tocopherol solution in a UV-Vis spectrophotometer at a maximum wavelength of 757 nm. The results showed that the sample of red fruit ethanol extract (Pandanus conoideus Lam.) Had total antioxidant activity with an activity of 1,392 x 10-3 g ATE / g extract.